Wireless mesh sensor networks with mobile devices: a comprehensive review - Meralto, C. (2017)
Mesh communications is emerging as a popular networking solution. Mesh networks have a decentralized and multihop design. These characteristics arouse interest for the research of the following features: cooperation, task distribution, scalability and communication with limited infrastructure support. This chapter studies relevant solutions in Wireless Sensor Networks (WSNs) with a mesh design that is used with mobile devices. The use of mobile devices on WSNs has recently grown due to: hardware evolution, large number of embedded sensors and daily high utilization of handheld devices. Consequently, novel requisites in the design and implementation of WSNs urge to be satisfied: autonomy of sensors battery and, efficient data exchange amongst sensors and the Internet. A real mesh testbed with two Layer 2 mesh solutions (Open802.11s and B.A.T.M.A.N) was implemented with different topologies. Some relevant results for a mesh network are discussed in terms of its scalability, performance and volatility.